Fatal traumatic brain injury, West Virginia, 1989-1998. - Adekoya, Nelson (Association of Schools of Public Health, 2004)
OBJECTIVE: The objective of this study was to describe fatal cases of traumatic brain injury (TBI) among West Virginia residents. METHODS: The authors analyzed data from the National Center for Health Statistics Multiple Cause of Death tapes for the period 1989-1998. They compared West Virginia's annualized average TBI death rate with the rates of other states and with the rate among U.S. residents for the same period. U.S. Bureau of Census population estimates were used as denominators. RESULTS: A total of 4,416 TBI deaths occurred in West Virginia in 1989-1998, for an annual average death rate of 23.6 per 100,000 population. From 1989 to 1998, TBI death rates declined 5% (p=0.4042). Seventy-five percent (n=3,315) of fatalities occurred among men. Adults > or =65 years of age accounted for the highest percentage of fatal injuries (n=1,135). The leading external causes of fatal TBI were: firearm-related (39% of reported fatalities), motor vehicles-related (34%), and fall-related (10%). Firearm-related TBI became the leading cause of TBI fatalities in 1991, surpassing motor vehicle-related TBI. Seventy-five percent of firearm-related TBI deaths were suicides (n=1,302). West Virginia's TBI death rate (23.6 per 100,000) was higher than the national rate (20.6 per 100,000). In 23 states, the average TBI death rates over the 10-year period were higher than West Virginia's. Whereas modest declines in TBI death rates occurred for motor vehicle-related and firearm-related causes in West Virginia, a concomitant 38% increase occurred in the fall-related TBI death rate during the decade. CONCLUSION: Data presented in this report can be used to develop targeted prevention programs in West Virginia.